Implementation of Role-Playing Methods for Early Childhood Language Development at TK Aisyiyah Sumber I - Wati, Dwi Purnomo; Hastuti, Isnaini Budi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to identify how the role‑playing method can improve language skills in early childhood learners and to explore the factors that influence its effectiveness. By simulating real‑life scenarios in a fun and interactive way, the method seeks to transform children who are typically quiet, passive, or lacking in confidence into active and self‑assured communicators. Methodology: Employing a qualitative approach, researchers observed and interviewed children aged 5–6 at Aisyiyah Sumber I Kindergarten. Data collection centered on systematic classroom observations of role‑play sessions and in‑depth interviews with both children and their teachers to gather insights into changes in communication behavior and the conditions supporting those changes. Results: Following the implementation of role play, children who had previously been reticent began to engage actively and confidently with peers, expressing ideas, feelings, and thoughts both spontaneously and voluntarily. Quantitative indicators of improvement included expanded vocabulary, more complex sentence structures, and stronger verbal interaction skills. Additionally, role play fostered social and emotional engagement, further reinforcing language development. Applications/Originality/Value: The findings demonstrate that the role‑playing method is an effective strategy for early‑childhood language learning. To sustain its benefits, educators and parents should collaborate to design scenarios that are engaging, meaningful, and age‑appropriate, and provide guided support throughout the activities. This research offers practical guidance for curriculum planners and caregivers seeking to enhance communicative competence and confidence in young learners.